Kenabian Maryam Perspektif Mufassir Andalusia - Suwandi, Yasmin Karima Fadilla (Proceedings of Student Symposium on Ushuluddin and Islamic Thought, 2024)
This research was conducted because there are differences of opinion among mufassir regarding the prophetic status of women, especially Maryam. Some commentators such as al-Alusi prefer to classify Maryam as a guardian of Allah SWT. However, Ibn Kathi>r and al-Razi are of the opinion that Maryam is considered a s}iddi>qah and not a prophet. However, Mufassir Andalusia has his own opinion on the issue of the prophethood of women, especially Maryam. The problem examined in this research is the interpretation of Andalusian mufassir regarding Maryam's prophetic verses and Maryam's prophetic status. The object of research is in surah al-Baqarah verse 253 and Maryam verse 19, which is supported by interpretations of other verses such as those in Surah Ali 'Imran verse 42. The aim of formulating this problem is to find the Andalusian interpreter's interpretation of the prophetic verse Maryam. This has implications for Maryam's prophetic status according to Andalusian commentators. The problem above is in the nature of library research, so this research uses descriptive analytical research methods. These two methods are used to explain the Andalusian mufassir's interpretation of surah al-Baqarah verse 253 and surah Maryam verse 19. The conclusion of this research is that according to the Andalusian mufassir they agree on Maryam's prophetic status because of Maryam's firm faith, the conception of Jesus, and the incident of Gabriel coming to Maryam is proof of Maryam's prophethood.